First report of cucurbit yellow vine disease caused by Serratia marcescens on cucurbit crops in Iowa - Mphande, Kephas; Beattie, Gwyn A; Gleason, Mark L (Plant disease, 2024)
Cucurbit yellow vine disease (CYVD) is caused by , vectored by squash bugs ( ), and is an emerging disease in many parts of the U.S. CYVD can cause 100% yield losses in cucurbits (Bruton et al., 2003). In the summer of 2021, at the Iowa State University Horticultural Research Station (HRS) in Gilbert, Iowa, we observed leaf yellowing, vine decline, and honey-brown discoloration of the phloem of acorn squash ( cv. Table Ace) plants in research fields that were infested with squash bugs. In 2022, we observed similar symptoms on pumpkin ( cv. Howden) and muskmelon ( cv. Athena) in different fields at the HRS and on giant pumpkins ( cv. Prizewinner) in Jones and Ringgold counties. For up to 3 symptomatic plants of each cucurbit species per location, a 20-cm-long stem section immediately above the soil line was excised, surface sterilized by immersion in 10% sodium hypochlorite and 70% ethanol for 2 min each, then triple rinsed in sterile water. The interior of the cross-section tissue was blotted on Luria agar amended with cycloheximide (100 μg/ml) and tetracycline (20 μg/ml) (Stock et al. 2003). Whitish translucent colonies developed after incubation at 28°C for 48 h. The genomic DNA of three isolates from symptomatic plants of muskmelon (MK01), pumpkin (HFP01), and giant pumpkin (AP01), was extracted using the DNeasy Blood and Tissue Kit (Qiagen, Germantown, MD). species-specific primers YV1 (5'-GGGACTTGCTCCCCGG-3') and YV4 (5'-AACGTCAATTGATGAACGTATTAAGT-3') (Bruton et al. 2003) were used to amplify part of the 16S rDNA gene, and the primers specific to S. marcescens CYVD strains A79F/A79R (Zhang et al., 2005) were used to amplify part of a major facilitatory superfamily (MFS) transporter gene strain. The sequences of the 16S rRNA PCR product for the three isolates were identical and were deposited in NCBI under Accession OR963533. They shared 100% (395/395 nt) identity with other CYVD strains (Rascoe et al. 2003) and those of other strains in NCBI. The sequences of the amplified region of the MFS transporter gene of the three isolates (NCBI Accession OR962261) were identical and showed a 98.8% (319/323 nt) identity to that of non-CYVD-causing strains, such as N10A28 (Accession CP033623.1). Koch's postulates were fulfilled by inoculating cv. Zephyr plants with either strain HFP01 or phosphate buffer saline (PBS) (10 plants per treatment) 1 wk after seeding by injecting 300 µl of bacteria (~10 CFU/ml) or PBS using a syringe needle. Plants were incubated at 28°C in a growth room for 4 wks. CYVD symptoms similar to those observed in the field developed on 7 out of 10 plants inoculated with strain HFP01 in one study, and 9 out 10 plants in a replicate study, with none of the PBS-inoculated plants showing CYVD symptoms. Bacteria were isolated from the symptomatic plants with selection on tetracycline. The PCR fragments amplified with YV1/YV4 and A79F/A79R were the same size as those of the pre-inoculation strain HFP01. To our knowledge this is the first report of CYVD in Iowa and in the Upper Midwest of the U.S. CYVD is a devastating disease that poses a significant threat to cucurbit production. This report can serve as an alert for the region's growers and for the development of effective management practices.